Investigation on psychosomatic status of entry quarantine personnel during the COVID-19 pandemic - SHEN,Shi-Hua (2022)
Abstract To investigate the anxiety, depression, fatigue and insomnia of the entry quarantine personnel during the COVID-19 pandemic, and the influencing factors of psychological status were also explored. The Self-Rating Anxiety Scale (SAS), Self-Rating Depression Scale (SDS), Fatigue severity scale (FSS) and the Insomnia Severity Index (ISI) of 630 entry quarantine personnel were performed and the correlation analysis of the four types of scales was performed. The incidence rates of anxiety, depression, fatigue and insomnia were 4.76%, 20.00%, 48.57% and 22.86%, respectively. There was a positive correlation between the four indicators. Univariate analysis showed that age, education level, occupation, continent and reasons for going abroad were the main influencing factors of psychosomatic status. The lower the age group, the higher the education level, and the healthier the psychosomatic health of the entry quarantine personnel. The psychological status of international students was healthier than that of the staff. The psychological condition of the quarantined people in Asia was healthier than that in other continents. 630 entry quarantine personnel had different degrees of anxiety, depression, fatigue and insomnia, there was a positive correlation between them. Age, education level, occupation, continent and reasons for going abroad were the main influencing factors of psychological status.